CCAAT/enhancer binding protein α predicts poorer prognosis and prevents energy starvation–induced cell death in hepatocellular carcinoma. Issue 3 (30th January 2015) - Lu, Guo‐Dong; Ang, Yang Huey; Zhou, Jing; Tamilarasi, Jegadeesan; Yan, Benedict; Lim, Yaw Chyn; Srivastava, Supriya; Salto‐Tellez, Manuel; Hui, Kam M.; Shen, Han‐Ming; Nguyen, Long N.; Tan, Bryan C.; et al.
Abstract : CCAAT enhancer binding protein α (C/EBPα) plays an essential role in cellular differentiation, growth, and energy metabolism. Here, we investigate the correlation between C/EBPα and hepatocellular carcinoma (HCC) patient outcomes and how C/EBPα protects cells against energy starvation. Expression of C/EBPα protein was increased in the majority of HCCs examined (191 pairs) compared with adjacent nontumor liver tissues in HCC tissue microarrays. Its upregulation was correlated significantly with poorer overall patient survival in both Kaplan‐Meier survival ( P  = 0.017) and multivariate Cox regression ( P  = 0.028) analyses. Stable C/EBPα‐silenced cells failed to establish xenograft tumors in nude mice due to extensive necrosis, consistent with increased necrosis in human C/EBPα‐deficient HCC nodules. Expression of C/EBPα protected HCC cells in vitro from glucose and glutamine starvation–induced cell death through autophagy‐involved lipid catabolism. Firstly, C/EBPα promoted lipid catabolism during starvation, while inhibition of fatty acid beta‐oxidation significantly sensitized cell death. Secondly, autophagy was activated in C/EBPα‐expressing cells, and the inhibition of autophagy by ATG7 knockdown or chloroquine treatment attenuated lipid catabolism and subsequently sensitized cell death. Finally, we identified TMEM166 as a key player in C/EBPα‐mediated autophagy induction and protection against starvation. Conclusion : The C/EBPα gene is important in that it links HCC carcinogenesis to autophagy‐mediated lipid metabolism and resistance to energy starvation; its expression in HCC predicts poorer patient prognosis. (Hepatology 2015;61:965–978)